Grammatical and Lexical Cohesion in Harry Potter and the Cursed Child Drama Script - Ayu Cahyati (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2019)
This study aims to describe grammatical and lexical cohesion and find out which one is the most dominant grammatical and lexical cohesion used in Harry Potter and the Cursed Child drama script. This study uses a qualitative descriptive method. The Source of the data in this study is the Harry Potter and the Cursed Child drama script. The data is collected through taking notes and Coding the data. The techniques of data analysis is done through presenting, describing, interpreting, and concluding the data. The result of this study shows that from 60 data which is grammatical cohesion is 40 data and lexical cohesion is 20 data. Grammatical cohesion device which is mostly seen in the object is reference, especially the personal reference that is expressed by the words â€œIâ€ and â€œyouâ€. The word â€œIâ€ refers to the speaker and â€œyouâ€ refers to the listener. The usage of reference aimed to refer to someone or something in order to avoid word repetition. Meanwhile, the lexical cohesion mostly used is repetition. The function of the repetition is mostly to make the sentence become varied and not awkward because the speakers keep on repeating the same word. Therefore, it can be concluded that, the grammatical cohesion mostly used is referenced with a percentage of 59.03%. Meanwhile, lexical cohesion is repetition with a percentage of 12.25%.